Role of Potassium-competitive Acid Blockers in the Treatment of Gastric Acid-related Disorders - Mun Young Cho; Yu Kyung Cho (Yong Chan Lee, 2023)
Owing to their superior pharmacokinetic and pharmacodynamic profiles, potassium-competitive acid blockers (P-CABs) score over proton pump inhibitors (PPIs) in the treatment of gastric acid-related disorders and may provide clinical benefit in the management of these conditions. Previous studies have compared P-CABs with PPIs for treatment of gastric acid-related disorders, and current data show that P-CABs are non-inferior to PPIs in the treatment of erosive esophagitis and as maintenance therapy. P-CABs are useful for effective healing and as maintenance medications in patients with severe esophagitis. These drugs also aid with healing of peptic ulcers and artificial ulcers secondary to gastric endoscopic submucosal dissection (ESD). Few studies have discussed prevention of delayed ulcer bleeding after gastric ESD and ulcers associated with long-term nonsteroidal anti-inflammatory drug administration. Well-controlled, large-scale prospective studies are warranted in future to compare P-CABs with PPIs.